Preparation method of long-service-life multi-disc type carbon-ceramic brake disc

By regulating the differential density matching of carbon/ceramic brake discs, the problem of low friction coefficient in existing carbon/ceramic brake materials under high-energy load and medium-low speed braking conditions is solved, and the effect of high friction coefficient and low wear is achieved. It is suitable for multi-disc carbon ceramic brake pairs for tracked military vehicles.

CN119859066APending Publication Date: 2025-04-22西安源创航空科技有限公司 +1

Patent Information

Application Number
CN202510213109.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing three-dimensional needle-punched carbon/ceramic brake materials have low friction coefficient and are unstable under high-performance conditions, which is difficult to meet the high-performance needs of military vehicles.

Method used

By controlling the density of prefabricated bodies, carbon-carbon matrix and carbon ceramic finished products, differentiated matching combinations of dynamic and static discs are adopted, with high density of dynamic and static discs (2.2-2.35g/cm3) and low density of static discs (1.8-1.9g/cm3), the synergistic effect of dynamic and static combination is achieved, the friction coefficient is maximized, and the wear is reduced.

Benefits of technology

It achieves high friction coefficient and low wear under high-energy load, medium and low-speed braking conditions, extends the service life of the brake disc, and is suitable for multi-disc carbon ceramic brake pairs for tracked military vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859066A_ABST
    Figure CN119859066A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a long-life multi-disc type carbon ceramic brake disc, which comprises the following steps: preparing a three-dimensional needling movable disc and static disc prefabricated body, performing chemical vapor deposition treatment on the prepared prefabricated body, machining the treated prefabricated body into a base body according to the size requirement of a finished product by adopting a machining method, and performing vacuum drying on the base body to obtain the long-life multi-disc type carbon ceramic brake disc. And respectively carrying out in-situ reaction densification on the carbon-carbon substrates of the movable disc and the static disc and the ceramic particles to obtain a high-density movable disc and a low-density static disc. The dynamic disc and the static disc are paired and subjected to differential matching, density regulation and control are strict, the density of the dynamic disc is high (2.2-2.35 g / cm < 3 >), the density of the static disc is low (1.8-1.9 g / cm < 3 >), dynamic and static cooperation and synergistic effect are achieved, the friction coefficient is maximized, abrasion is minimized, and the service life of a product is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of multi-disc carbon-ceramic brake discs, and in particular relates to a method for preparing a long-life multi-disc carbon-ceramic brake disc. Background Art

[0002] With the rapid development of national defense, new combat requirements of all-weather, high-speed and high-energy load are put forward. The performance of military vehicles such as tanks, armored vehicles, and amphibious vehicles also needs to be comprehensively improved, especially the performance requirements of friction materials in the braking system are more stringent. Among them, high performance and light weight are important indicators for measuring friction materials. At present, due to the special braking conditions of military vehicles, the replacement frequency of brake pairs is higher than that of passenger cars, and generally does not exceed 10,000 kilometers.

[0003] Carbon / ceramic brake discs not only maintain the advantages of carbon / carbon composite materials, such as high temperature resistance, low density, smooth braking, low wear rate, and large heat capacity, but also overcome the shortcomings of carbon / carbon brake materials such as low static friction coefficient, poor wet performance, weak matrix strength, and poor environmental adaptability, meeting the high performance and lightweight indicators of the new generation of brake materials. They are now mass-produced and applied to aircraft multi-disc brake assemblies. Multi-disc carbon-ceramic brake discs are generally composed of multiple dynamic discs and static discs. During the braking process, the dynamic and static discs cooperate with each other to play the role of braking. The structure is different from the brake disc with a ventilation structure (CN221665160U), so it has higher performance requirements.

[0004] CN 118324536 A discloses a method for preparing a carbon / ceramic brake disc with a surface ceramic wear-resistant coating. The carbon / ceramic brake disc with a SiC / Si ceramic wear-resistant coating structure is prepared by chemical vapor deposition, atmospheric pressure pressing, and reaction infiltration after secondary deposition. The low friction coefficient and instability during braking are effectively solved, and the braking performance of the carbon / ceramic brake disc is improved. CN 117682886A discloses a method for preparing a sandwich structure carbon / ceramic brake disc for automobiles. A three-dimensional needle-punched preform is first prepared, and then chemical vapor deposition treatment is performed. Then, a substrate is machined and a wear-resistant coating is applied to the substrate. A high-density carbon-ceramic composite material is generated by high-temperature heat treatment, which can improve the wear resistance of the carbon / ceramic brake material and extend its service life. However, the above materials are generally used in traditional commercial vehicles. In the past two years, military vehicle braking has also been trying and exploring carbon / ceramic brake discs, but because its performance is different from that of traditional commercial vehicles, it has not yet been applied in batches.

[0005] The present invention prepares a multi-disc carbon-ceramic brake pair for tracked military vehicles under braking conditions of large load and medium and low speed (40-80km / h), and adjusts and designs the density of the preform, carbon-carbon matrix and carbon-ceramic finished product according to different disc types to form a special brake disc assembly for special working conditions. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing a long-life multi-disc carbon-ceramic brake disc based on the existing three-dimensional needle-punched carbon / ceramic brake material in view of the above-mentioned shortcomings. By adjusting and designing the density of the preform, the carbon-carbon matrix and the carbon-ceramic finished product, a high density of the dynamic disc and a low density of the static disc are achieved, and the dynamic and static coordination effect is achieved to maximize the friction coefficient and minimize the wear.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0008] A method for preparing a long-life multi-disc carbon-ceramic brake disc, the method comprising the following steps:

[0009] S1. Preform preparation

[0010] The 0° non-wefted fabric, the 90° non-wefted fabric and the web are stacked together in an alternating manner, and then the needle-punched fibers are inserted to prepare a three-dimensional needle-punched moving disk preform and a static disk preform respectively;

[0011] S2. Preform deposition

[0012] The moving disk preform and the static disk preform prepared in S1 are placed in a chemical vapor deposition furnace for deposition treatment. When the temperature in the deposition furnace reaches 1085-1115° C., hydrocarbon gas is introduced into the deposition furnace as a gas source. The hydrocarbon gas is diffused inside the preform at a pressure of 1.25-1.45 kPa, adsorbed on the surface of the preform and pyrolysis reaction occurs, thereby obtaining the deposited moving disk and static disk preforms.

[0013] S3. Machining

[0014] The moving disk and the static disk preforms after S2 deposition are machined by a machining method to produce the moving disk and the static disk carbon-carbon matrix with holes and grooves of characteristic size according to the finished product size requirements;

[0015] S4, in-situ reaction densification

[0016] The carbon-carbon matrix of the moving disk and the static disk after S3 machining is reacted in situ with ceramic particles to increase density, thereby obtaining a high-density moving disk and a low-density static disk; the ceramic particles are obtained by mixing SiC, WC and TiC in a mass ratio of (50-60)%: (30-45)%: (5-10)%.

[0017] Preferably, when preparing the movable disk preform in S1, every 2-3 layers of non-woven fabric and 1-2 layers of mesh are superimposed and needle-punched until the product size is reached, and the density of the movable disk preform is finally controlled to be (0.6-0.7) g / cm 3When preparing the static disk preform, each layer of non-woven fabric is superimposed with a layer of mesh tire and needle-punched until the product size is reached, and the density of the static disk preform is finally controlled to be (0.35-0.45) g / cm 3 .

[0018] Preferably, the hydrocarbon gas in S2 is any one of methane, acetylene, propane or propylene.

[0019] Preferably, the hydrocarbon gas flow rate for the moving disk preform deposition process in S2 is (15-20) m 3 / h, and the duration is (150-250)h, until the density of the moving disk carbon matrix reaches (1.2-1.35)g / cm 3 ; The hydrocarbon gas flow rate of the static disk preform deposition treatment is (10-15) m 3 / h, and the duration is (150-250)h, until the density of the static disk carbon matrix reaches (1.4-1.65)g / cm 3 .

[0020] Preferably, the amount of ceramic particles added during the in-situ reaction of the moving disk in S4 is (2-4) times the weight of the carbon content of the current moving disk carbon-carbon matrix, and the amount of ceramic particles added during the in-situ reaction of the static disk is (1.5-3) times the weight of the carbon content of the current static disk carbon-carbon matrix, and the carbon content is the sum of deposited carbon and pyrolytic carbon.

[0021] Preferably, the conditions for the in-situ reaction in S4 are: temperature of 1600-1700° C. and vacuum state.

[0022] Preferably, the density of the high-density moving disk finally formed in S4 is (2.2-2.35) g / cm 3 The density of the low-density static disk is (1.8-1.9) g / cm 3 .

[0023] Compared with the prior art, the present invention has the following significant technical effects:

[0024] 1. The conventional multi-disc carbon ceramic friction pair generally uses the same process and the same material for the dynamic and static disks. However, in the present invention, the dynamic and static disks are matched with differentiated matching, and the density is strictly controlled. The dynamic disk has a high density (2.2-2.35g / cm 3 ), static disk low density (1.8-1.9g / cm 3 ), the dynamic and static coordination works together to maximize the friction coefficient, minimize wear and extend product life.

[0025] 2. The moving disc is the main load-bearing component during braking. When preparing the moving disc preform, the present invention strengthens the main support body (without weft cloth) so that it can bear a larger load.

[0026] 3. The various disc types in the multi-disc assembly of the present invention have different functions and different product implementation processes, and can be further extended to other application scenarios of carbon ceramic materials, such as clutch plates, military vehicle brakes, and urban vehicle brakes, with strong adaptability.

[0027] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a microscopic photograph of the surface microstructure of the friction surface of the moving disc of the long-life multi-disc carbon-ceramic brake disc of Example 1 of the present invention and a commercial multi-disc carbon / ceramic brake disc after a 1000km braking test; a: the long-life multi-disc carbon-ceramic brake disc of Example 1, b: a commercial multi-disc carbon / ceramic brake disc, c: an enlarged view of a, d: an enlarged view of b.

[0029] Figure 2 This is an energy spectrum diagram of the friction surface of the long-life multi-disc carbon-ceramic brake disc prepared in Example 1 of the present invention after a 1000km braking test, wherein Figures a, b, and c are electron images, Si Kα1, and C Kα1,2 energy spectra, respectively.

[0030] Figure 3 This is the energy spectrum diagram of the friction surface of a commercial multi-disc brake disc after a 1000km braking test, where Figures a, b, and c are the electron image, Si Kα1, and C Kα1,2 energy spectra, respectively. DETAILED DESCRIPTION

[0031] Example 1

[0032] This embodiment is a method for preparing a long-life multi-disc carbon-ceramic brake disc, the method comprising the following steps:

[0033] S1. Preform preparation

[0034] A three-dimensional needle-punched preform is prepared by stacking 0° non-weft cloth, 90° non-weft cloth and mesh tire together and then inserting needle-punched fibers. When preparing the moving disk preform, every 2 layers of non-weft cloth and 1 layer of mesh tire are stacked and needle-punched; when preparing the static disk preform, every 1 layer of non-weft cloth and 1 layer of mesh tire are stacked and needle-punched until the product size is reached. Finally, the density of the moving disk preform is controlled at 0.65g / cm 3 , the density of the static disk preform is 0.4g / cm 3 .

[0035] S2. Preform deposition

[0036] The moving disk and static disk preforms prepared by S1 are placed in a chemical vapor deposition furnace for deposition. When the temperature in the deposition furnace reaches 1100°C, hydrocarbon gas (methane) is introduced into the deposition furnace as a gas source. At this time, under a pressure of 1.35 kPa, the hydrocarbon gas diffuses inside the preform, adsorbs on the surface of the preform and undergoes a pyrolysis reaction, achieving a densification effect, and obtaining the moving disk and static disk preforms after deposition. The hydrocarbon gas flow rate for the moving disk deposition process is 15m 3 / h, the hydrocarbon gas flow rate for static plate deposition treatment is 12m 3 / h, lasting for 200h, until the density of the moving disk carbon matrix reaches 1.35g / cm 3 The density of static carbon matrix is ​​1.6g / cm 3 .

[0037] S3. Machining

[0038] The moving disk and the static disk preforms after S2 deposition are processed by mechanical processing to produce the moving disk and the static disk carbon-carbon matrix with characteristic dimensions such as holes and grooves according to the finished product size requirements.

[0039] S4, in-situ reaction densification

[0040] The carbon-carbon matrix of the moving disk and the static disk after S3 machining is reacted in situ with ceramic particles (SiC: WC: TiC mixed in a mass ratio of 50%: 45%: 5%). The carbon content is calculated according to the density of the carbon-carbon matrix after the previous deposition (the sum of deposited carbon and pyrolytic carbon). The amount of ceramic particles added during the in-situ reaction of the moving disk is 3 times the weight of the carbon content of the current moving disk carbon-carbon matrix, and the amount of ceramic particles added during the in-situ reaction of the static disk is 2 times the weight of the carbon content of the current static disk carbon-carbon matrix. During the in-situ reaction, the ceramic particles adhere to the surface of the carbon-carbon matrix, so that the matrix is ​​completely covered by the ceramic particles (including special parts such as holes and grooves), and directly react chemically at a high temperature of 1650°C and in a vacuum state to form a wear-resistant phase. Finally, a high-density moving disk of 2.26g / cm is formed. 3 And low density static disk 1.8g / cm 3 .

[0041] The long-life multi-disc carbon-ceramic brake disc prepared in this embodiment and a commercial multi-disc carbon-ceramic brake disc (a certain ordnance research institute, model QCE-03 product) were subjected to friction and wear tests. The test conditions were 60 km / h braking and a braking distance of 1000 km. The two products were tested on the same bench with the same test conditions. The maximum outer profile of the product was 452 mm. The results are shown in Table 1.

[0042] Table 1 Friction coefficient and wear test results of multi-disc carbon ceramic brake disc

[0043]

[0044]

[0045] As can be seen from Table 1, the multi-disc brake disc of the present invention (Example 1) has a higher friction coefficient and lower wear than a certain commercial multi-disc carbon / ceramic brake disc, especially the friction coefficient, which is significantly higher than that of a certain commercial multi-disc carbon / ceramic brake disc, and can meet the requirements of use under high-energy load and medium and low speed (40-80km / h) braking conditions.

[0046] Because in this structure, the moving disc directly bears the torque and the working conditions are relatively more severe, therefore, after the friction and wear test, the surface microstructure microscopic analysis and energy spectrum analysis of the friction surface of the multi-disc assembly in the present invention are only described using the moving disc as an example.

[0047] In FIG. 1 , a and b are respectively microscopic micrographs of the surface microstructure of the friction surface of the long-life multi-disc carbon-ceramic brake disc of Example 1 of the present invention and a commercial multi-disc carbon / ceramic brake disc after a 1000 km braking test, indicating that the friction surface of the carbon-ceramic material is composed of carbon fiber, deposited carbon and SiC multiphases. In addition, during the friction process of the product, the micro-protrusions on the surface of the material are continuously sheared and detached, and the wear particles generated are scattered on the surface, and even some of the wear particles are filled into the gaps of the friction surface under the action of pressure. The specific performance is the increase in wear, and at the microscopic level, the wear particles of the long-life multi-disc carbon-ceramic brake disc prepared by the present invention are significantly less than those of the commercial multi-disc carbon-ceramic brake disc. Figure 1c and Figure 1d They are Figure 1a and Figure 1b From the enlarged image, it can be seen from the red circle that obvious cracks have appeared at the ends of the fibers in the commercial multi-disc carbon / ceramic brake disc body, while the fiber surface morphology in the long-life multi-disc carbon-ceramic brake disc prepared by the present invention remains intact, further indicating that it has better mechanical properties and can withstand greater loads.

[0048] Figure 2 and Figure 3 Figures 2 and 3 show energy spectra of the friction surfaces of the long-life multi-disc carbon-ceramic brake disc of Example 1 of the present invention and a commercial multi-disc brake disc after a 1000km braking test. By comparison, it can be seen that the long-life multi-disc carbon-ceramic brake disc of the present invention contains more Si elements, and the Si element is provided by the main friction particles SiC in the carbon-ceramic material. This also explains why the long-life multi-disc carbon-ceramic brake disc prepared by the present invention has a higher friction coefficient.

[0049] Example 2

[0050] This embodiment is a method for preparing a long-life multi-disc carbon-ceramic brake disc, the method comprising the following steps:

[0051] S1. Preform preparation

[0052] The 0° non-woven fabric, 90° non-woven fabric and mesh are stacked together and then needle-punched fibers are inserted to prepare a three-dimensional needle-punched preform. When preparing the moving disk preform, every 2 layers of non-woven fabric and 1 layer of mesh are stacked and needle-punched; when preparing the static disk preform, every 1 layer of non-woven fabric and 1 layer of mesh are stacked and needle-punched until the product size is reached. Finally, the density of the moving disk preform is controlled at 0.6g / cm 3 , the density of the static disk preform is 0.35g / cm 3 .

[0053] S2. Preform deposition

[0054] The moving disk and static disk preforms prepared by S1 are placed in a chemical vapor deposition furnace for deposition. When the temperature in the deposition furnace reaches 1085°C, hydrocarbon gas (acetylene) is introduced into the deposition furnace as a gas source. At this time, under a pressure of 1.25 kPa, the hydrocarbon gas diffuses inside the preform, adsorbs on the surface of the preform and undergoes a pyrolysis reaction, achieving a densification effect, and obtaining the moving disk and static disk preforms after deposition. The hydrocarbon gas flow rate for the moving disk deposition process is 18m 3 / h, the hydrocarbon gas flow rate for static plate deposition treatment is 13m 3 / h, lasting for 150h, until the density of the moving disk carbon matrix reaches 1.33g / cm 3 The density of static carbon matrix is ​​1.48g / cm 3 .

[0055] S3. Machining

[0056] The moving disk and the static disk preforms after S2 deposition are processed by mechanical processing to produce the moving disk and the static disk carbon-carbon matrix with characteristic dimensions such as holes and grooves according to the finished product size requirements.

[0057] S4, in-situ reaction densification

[0058] The carbon-carbon matrix of the moving disk and the static disk after S3 machining is reacted in situ with ceramic particles (SiC: WC: TiC mixed in a mass ratio of 55%: 38%: 7%). The carbon content is calculated (the sum of deposited carbon and pyrolytic carbon) according to the density of the carbon-carbon matrix after the previous deposition. The amount of ceramic particles added during the in-situ reaction of the moving disk is twice the weight of the carbon content of the current moving disk carbon-carbon matrix, and the amount of ceramic particles added during the in-situ reaction of the static disk is 1.5 times the weight of the carbon content of the current static disk carbon-carbon matrix. During the in-situ reaction, the ceramic particles adhere to the surface of the carbon-carbon matrix, so that the matrix is ​​completely covered by the ceramic particles (including special parts such as holes and grooves), and directly react chemically at a high temperature of 1600°C and in a vacuum state to form a wear-resistant phase. Finally, a high-density moving disk of 2.21g / cm is formed. 3 And low density static disk 1.83g / cm 3.

[0059] Example 3

[0060] This embodiment is a method for preparing a long-life multi-disc carbon-ceramic brake disc, the method comprising the following steps:

[0061] S1. Preform preparation

[0062] A three-dimensional needle-punched preform is prepared by stacking 0° non-weft cloth, 90° non-weft cloth and mesh tire together and then inserting needle-punched fibers. When preparing the moving disk preform, every 3 layers of non-weft cloth and 2 layers of mesh tire are stacked and needle-punched; when preparing the static disk preform, every 1 layer of non-weft cloth and 1 layer of mesh tire are stacked and needle-punched until the product size is reached. Finally, the density of the moving disk preform is controlled at 0.7g / cm 3 , the density of the static disk preform is 0.45g / cm 3 .

[0063] S2. Preform deposition

[0064] The moving disk and static disk preforms prepared by S1 are placed in a chemical vapor deposition furnace for deposition. When the temperature in the deposition furnace reaches 1115°C, hydrocarbon gas (propylene) is introduced into the deposition furnace as a gas source. At this time, under a pressure of 1.45 kPa, the hydrocarbon gas diffuses inside the preform, adsorbs on the surface of the preform and undergoes a pyrolysis reaction, achieving a densification effect, and obtaining the moving disk and static disk preforms after deposition. The hydrocarbon gas flow rate for the moving disk deposition process is 20m 3 / h, the hydrocarbon gas flow rate for static plate deposition treatment is 15m 3 / h, lasting for 250h, until the density of the moving disk carbon matrix reaches 1.34g / cm 3 The density of static carbon matrix is ​​1.65g / cm 3 .

[0065] S3. Machining

[0066] The moving disk and the static disk preforms after S2 deposition are processed by mechanical processing to produce the moving disk and the static disk carbon-carbon matrix with characteristic dimensions such as holes and grooves according to the finished product size requirements.

[0067] S4, in-situ reaction densification

[0068] The carbon-carbon matrix of the moving disk and the static disk after S3 machining is reacted in situ with ceramic particles (SiC: WC: TiC mixed in a mass ratio of 58%: 32%: 10%). The carbon content is calculated (the sum of deposited carbon and pyrolytic carbon) according to the density of the carbon-carbon matrix after the previous deposition. The amount of ceramic particles added during the in-situ reaction of the moving disk is 4 times the weight of the carbon content of the current moving disk carbon-carbon matrix, and the amount of ceramic particles added during the in-situ reaction of the static disk is 3 times the weight of the carbon content of the current static disk carbon-carbon matrix. During the in-situ reaction, the ceramic particles adhere to the surface of the carbon-carbon matrix, so that the matrix is ​​completely covered by the ceramic particles (including special parts such as holes and grooves). At a high temperature of 1700°C and in a vacuum state, a chemical reaction is directly carried out to form a wear-resistant phase. Finally, a high-density moving disk of 2.34g / cm is formed. 3 And low density static disk 1.9g / cm 3 .

[0069] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a long-life multi-disc carbon ceramic brake disc, characterized in that: The method comprises the following steps: S1. Preform preparation The 0° non-wefted fabric, the 90° non-wefted fabric and the web are stacked together in an alternating manner, and then the needle-punched fibers are inserted to prepare a three-dimensional needle-punched moving disk preform and a static disk preform respectively; S2. Preform deposition The moving disk preform and the static disk preform prepared in S1 are placed in a chemical vapor deposition furnace for deposition treatment. When the temperature in the deposition furnace reaches 1085-1115° C., hydrocarbon gas is introduced into the deposition furnace as a gas source. The hydrocarbon gas is diffused inside the preform at a pressure of 1.25-1.45 kPa, adsorbed on the surface of the preform and pyrolysis reaction occurs, thereby obtaining the deposited moving disk and static disk preforms. S3. Machining The moving disk and the static disk preforms after S2 deposition are machined by a machining method to produce the moving disk and the static disk carbon-carbon matrix with holes and grooves of characteristic size according to the finished product size requirements; S4, in-situ reaction densification The carbon-carbon matrix of the moving disk and the static disk after S3 machining is reacted in situ with ceramic particles to increase density, thereby obtaining a high-density moving disk and a low-density static disk; the ceramic particles are obtained by mixing SiC, WC and TiC in a mass ratio of (50-60)%: (30-45)%: (5-10)%.

2. The method according to claim 1, characterized in that When preparing the moving disk preform in S1, every 2-3 layers of non-woven fabric and 1-2 layers of mesh are superimposed and needled until the product size is reached, and the density of the moving disk preform is finally controlled to be (0.6-0.7) g / cm 3 .

3. The method according to claim 1, characterized in that When preparing the static disk preform in S1, each layer of the non-woven fabric is superimposed and needle-punched with a layer of the mesh tire until the product size is reached, and the density of the static disk preform is finally controlled to be (0.35-0.45) g / cm 3 .

4. The method according to claim 1, characterized in that: The hydrocarbon gas in S2 is any one of methane, acetylene, propane or propylene.

5. The method according to claim 1, characterized in that The hydrocarbon gas flow rate for the deposition treatment of the moving disk preform in S2 is (15-20) m 3 / h, and the duration is (150-250)h, until the density of the moving disk carbon matrix reaches (1.2-1.35)g / cm 3 .

6. The method according to claim 1, characterized in that The hydrocarbon gas flow rate for the static plate preform deposition process in S2 is (10-15) m 3 / h, and the duration is (150-250)h, until the density of the static disk carbon matrix reaches (1.4-1.65)g / cm 3 .

7. The method according to claim 1, characterized in that The amount of ceramic particles added during the in-situ reaction of the moving disk in S4 is (2-4) times the weight of the carbon content of the current moving disk carbon-carbon matrix, and the carbon content is the sum of deposited carbon and pyrolytic carbon.

8. The method according to claim 1, characterized in that The amount of ceramic particles added during the in-situ reaction of the static plate in S4 is (1.5-3) times the weight of the carbon content of the current static plate carbon matrix, and the carbon content is the sum of the deposited carbon and the pyrolytic carbon.

9. The method according to claim 1, characterized in that: The conditions for the in-situ reaction in S4 are: temperature of 1600-1700° C. and vacuum state.

10. The method according to claim 1, characterized in that The density of the high-density moving disk finally formed in S4 is (2.2-2.35) g / cm 3 The density of the low-density static disk is (1.8-1.9) g / cm 3 .

Citation Information

Patent Citations

  • Preparation method of sandwich structure carbon / ceramic brake disc for automobile

    CN117682886A

  • Preparation method of carbon / ceramic brake disc with surface ceramic wear-resistant coating

    CN118324536A

  • Carbon-ceramic brake disc for heavy-duty truck

    CN221665160U

Cited By

  • Carbon / carbon gas guide cylinder and preparation method thereof

    CN121537219A